GURU MENDONGENG KEARIFAN LOKAL BANYUMASAN - Sugeng Priyadi; Karton Karton; Ningsih Widayati (Khazanah Pendidikan, 2015)
Teachers skills in the collection and writing of folklore needs to be improved so that the cultural heritage of ancestors can be preserved. Furthermore, teachers develop learning model with storytelling folklore virtue that can be absorbed by the students. Learning model mythlogos- ethos could explain the mandate contained in folklore. The mandate is a form of local wisdom through character education. Keywords: folktale, local wisdom